A BLOCKCHAIN SYSTEM FOR DIGITAL SERTIFICATE VERIFICATION ON E-LEARNING - Dewi Setiowati (Lambung Mangkurat University, 2021)
The process of educational informatization in the digital era of big data is one of the significant changes in the transformation of the educational model from traditional classrooms (face to face) to online teaching and learning based, which brings innovations from various e-learning. E-Learning is distance learning that uses computer technology, computer networks and the internet. The E-Learning system in higher education in Indonesia which is still centralized is a problem in developing E-Learning in this research in implementing the Independent Campus Policy, one of the manifestations of student-centered and decentralized learning launched by the Ministry of Education and Culture (Kemdikbud). This research takes advantage of blockchain technology to achieve breakthrough E-Learning in Higher Education that is not centralized or decentralized. Blockchain technology provides the advantages of decentralized digital certificate issuance as well as secure storage using the Ethereum blockchain. The results show blockchain technology to solve weaknesses in the field of online education based on Merdeka Campus, namely the issuance of certificates as evidence of student learning outcomes in the form of a formal digital certificate in decentralized E-Learning and insecurity in storage for verification using the Ethereum blockchain. The digital certificate from the transaction will identify block hash, gas usage, block number and block time as different private keys.Keywords: E-Learning, Independent Campus, Blockchain, Digital Certificate Verification Abstrak Proses informatisasi pendidikan di era digital data besar (big data) merupakan salah satu perubahan signifikan transformasi model pendidikan dari kelas trandisional (tatap muka) menjadi berbasis belajar-mengajar secara online, yang membawa inovasi dari berbagai e-learning. E-Learning adalah pembelajaran jarak jauh yang menggunakan teknologi komputer, jaringan komputer, dan internet. Sistem E-Learning pada Pendidikan tinggi di Indonesia yang masih terpusat menjadi permasalahan pengembangan E-Learning penelitian ini dalam menerapkan Kebijakan Kampus Merdeka salah satu perwujudan pembelajaran berpusat pada mahasiswa (student centered learning) dan terdesentralisasi yang diluncurkan oleh Kementerian Pendidikan dan Kebudayaan (Kemdikbud). Penelitian ini mengambil keunggulan teknologi blockchain agar dicapai terobosan E-Learning pada Pendidikan Tinggi yang tidak terpusat atau terdesentralisasi. Teknologi blockchain memberikan keunggulan penerbitan sertifikat digital terdesentralisasi serta penyimpanan aman menggunakan Ethereum blockchain. Hasil penelitian menunjukkan teknologi blockchain menyelesaikan kelemahan di bidang pendidikan online berbasis Kampus Merdeka yaitu penerbitan sertifikat digital sebagai bukti hasil belajar mahasiswa berupa sertifikat digital secara legal formal pada E-Learning secara terdesentralisasi dan ketidakamanan dalam penyimpanan untuk verifikasi sertifikat digital menggunakan Ethereum blockchain. Sertifikat digital hasil transaksi tersebut akan teridentifikasi block hash, gas usage, block number dan block time sebagai private key yang berbeda satu dengan lainnya.Kata kunci: E-Learning, Kampus Merdeka, Blockchain, Verifikasi Sertifikat Digital